2021
DOI: 10.1021/acs.chemrev.0c00977
|View full text |Cite
|
Sign up to set email alerts
|

Biomedicine Meets Fenton Chemistry

Abstract: Since the first connection between Fenton chemistry and biomedicine, numerous studies have been presented in this field. Comprehensive presentation of the guidance from Fenton chemistry and a summary of its representative applications in cancer therapy would help us understand and promote the further development of this field. This comprehensive review first supplies basic information regarding Fenton chemistry, including Fenton reactions and Fenton-like reactions. Subsequently, the current progress of Fenton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
294
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(323 citation statements)
references
References 332 publications
4
294
0
1
Order By: Relevance
“…Generally, Fenton reaction involves the reaction of ferrous ions (Fe 2+ ) with hydrogen peroxide (H 2 O 2 ), and then produces hydroxyl radicals (·OH) to destruct various cellular organelles, damage the DNA, and disrupt the vasculatures in tumor sites. Aside from Fe‐based NPs, nanocomposites based on several other metal elements such as Cu, Mn, Ag, and Co can also mediate Fenton‐like reactions to realize CDT (Tang et al, 2021). As H 2 O 2 , the substrate of CDT, is often present in tumor regions at higher levels than in normal tissues, CDT is considered as a highly specific therapeutic strategy with low systemic toxicity.…”
Section: Nanostrategy‐mediated Combination Therapy For Mdr Reversalmentioning
confidence: 99%
“…Generally, Fenton reaction involves the reaction of ferrous ions (Fe 2+ ) with hydrogen peroxide (H 2 O 2 ), and then produces hydroxyl radicals (·OH) to destruct various cellular organelles, damage the DNA, and disrupt the vasculatures in tumor sites. Aside from Fe‐based NPs, nanocomposites based on several other metal elements such as Cu, Mn, Ag, and Co can also mediate Fenton‐like reactions to realize CDT (Tang et al, 2021). As H 2 O 2 , the substrate of CDT, is often present in tumor regions at higher levels than in normal tissues, CDT is considered as a highly specific therapeutic strategy with low systemic toxicity.…”
Section: Nanostrategy‐mediated Combination Therapy For Mdr Reversalmentioning
confidence: 99%
“…It is well-established that the antitumoral activities of the ferrocene unit are activated mainly through the Fenton-like reaction with endogenous hydrogen peroxide in cancer cells to produce reactive cOH. 11,20,21 Therefore, the efficacy of cOH generation was measured to investigated the potential antitumor activity of ferrocene compound by adding F1-F4 to a mixture of H 2 O 2 and methylene blue (Table 2). In the studied compounds, F1 are inefficient compared to F2-F4 in cOH generation.…”
Section: In Vitro Anticancer Activities and Structure-activity Relationshipmentioning
confidence: 99%
“…Previous report showed that semiconductor could transfer electron from its conduction band to H 2 O 2 under irradiation, thus generating COH radicals. [21] If so,s ince H 2 O 2 is upregulated in hypoxic tumor, [22] the generated COH radicals in the decomposition of H 2 O 2 , which possess strong oxidation ability, [23] could cause huge oxidation damage to cancer cells.T he H 2 O 2 decomposition was assayed by DPD method. [24] However,a sobserved in Figure S11a-c )g eneration could be dictated by the interfacial electron transfer process (type Im echanisms) drove by photoexcitation.…”
Section: Angewandte Chemiementioning
confidence: 99%